Role of Time-Driven Resource-Consumption Accounting in Strategic Cost Reduction and Support of Supply Chain Management - Al-Matari, Ebrahim Mohammed; Al-Hibari, Adeeb Abdulwahab (ExcelingTech, 2019)
The study aims to developResource-Consumption Accounting (RCA) by transforming the activities embodied in this approach fromtherigid multiple driversto aflexible unique time-driven driver by support pf supply chain management (SCM). This developmentis intended to overcome the criticisms directed at RCA,activating its role firstly in real cost reduction according to the production capacity mechanism and, secondly, in supply chain management support. The study adopts a theoretical descriptive approach,conceivingthe positives of RCA, Time-Driven Activity-Based Costing in an attempt to create a new approach that integrates the advantages of both approaches in order to reduce cost. It is concluded that Time-Driven Resource-Consumption Accounting (TDRCA) can lead to a real cost reduction and at the same timesupport supply chain management.